Good self, bad self : transforming your worst qualities into your biggest assets - Smith, Judy (Tantor, 2012)
One of America's best-known crisis managers reveals the secrets to overcoming a personal crisis, empowering listeners to become stronger people and fully recover from a damaging experience, whether a relationship crisis or business disaster.